Bhil Dialects and Khandesi : A Linguistics Analysis - (:unkn) unknown (Vishveshvaranand Vishva Bandhu Institute of Sanskrit and Indological Studies, Panjab University, Hoshiarpur, 1978)
In this book the author tries to linguistically analyse the similarities and variations of Bhil Dialects and Khandesi
Keywords: Linguistics; Bhili; English